Induction of a T-cell mediated suppressor activity by soluble products from antigen-specific helper/inducer human T-cell lines. - Fischer, A; Beverley, P; Feldmann, M; Smith, S (1983)
Influenza virus-specific (A/X31) long-term cultured human T-cell lines belonging to the helper/inducer T-cell set, produce high potency antigen specific helper factors which induce in vitro antibody production to A/X31 by autologous B cells, as well as small and variable amounts of non-specific helper factors. When added to unseparated peripheral blood mononuclear cells, both cultured T cells and their supernatants suppress in vitro antibody synthesis as measured by a solid phase enzyme-linked immunoassay, and T-cell proliferation to antigens and allogeneic cells, but not to mitogens. This phenomenon was further analysed and could be separated into several steps: (i) the production of suppressor inducer factor(s) by the T-cell lines which are distinct from the helper molecules; (ii) activation of T cells belonging to the suppressor/cytotoxic subset as defined by monoclonal antibodies, a process which is antigen-independent and non-genetically restricted, and is optimal with 18 hr incubation; (iii) the activated T cells non-specific suppress antibody production and antigen-induced or allogeneic cell-induced T-cell proliferation. Thus, antigen-specifically activated T-inducer cells exert multiple activities, including specific and non-specific help and non-specific induction of T suppressor cells.